Right for employees working for an employer outside the limits of the City of Montreal, to absent themselves for two hours, without loss of pay, in order to vote as electors on the City of Montreal elections — Applications of article 328 of the Charter of the City of Montreal

(untitled) (Département des relations industrielles de l’Université Laval, 1961)
SummaryThe Charter of the City of Montreal does not require that, in order to be an elector, a person should either reside or work within the City limits. Article 328 not only gives to any elector the right to quit his work; it also imposes upon the employer the obligation not to reduce an elector's salary. Such an obligation is decreed as a consequence of the employee's right freely to quit his work, and according to the charter, this right does not vary according to the elector's place of work.United Steelworkers of America Local 5063 and Dominion Steel and Coal Corporation Ltd (Canadian Bridge — Truscon Steel Works); Montreal, March 14th 1961; Jean Beetz, Arbitrator.